Spatial distribution of supratentorial diffuse gliomas: A retrospective study of 990 cases - Li, Gen; Yin, Chuandong; Zhang, Chuanhao; Xue, Bowen; Yang, Zuocheng; Li, Zhenye; Pan, Yuesong; Hou, Zonggang; Hao, Shuyu; Yu, Lanbing; Ji, Nan; Gao, Zhixian; et al. (Frontiers in Oncology, 2023)
Background Gliomas distribute unevenly in the supratentorial brain space. Many factors were linked to tumor locations. This study aims to describe a more detailed distributing pattern of these tumors with age and pathological factors concerned. Methods A consecutive series of 990 adult patients with newly-diagnosed supratentorial diffuse gliomas who underwent resection in Beijing Tiantan Hospital between January 2013 and January 2017 were retrospectively reviewed. For each patient, the anatomic locations were identified by the preoperative MRI, and the pathological subtypes were reviewed for histological grade and molecular status (if any) from his medical record. The MNI template was manually segmented to measure each anatomic location’s volume, and its invaded ratio was then adjusted by the volume to calculate the frequency density. Factors of age and pathological subtypes were also compared among locations. Results The insulae, hippocampi, and corpus callosum were locations of the densest frequencies. The frequency density decreased from the anterior to posterior (frontal - motor region - sensory region - parietal - occipital), while the grade (p < 0.0001) and the proportion of IDH-wt (p < 0.0001) increased. More tumors invading the right basal ganglion were MGMT-mt (p = 0.0007), and more of those invading the left frontal were TERT-wt (p = 0.0256). Age varied among locations and pathological subtypes. Conclusions This study demonstrated more detailed spatial disproportions of supratentorial gliomas. There are potential interactions among age, pathological subtypes, and tumor locations.